2003
DOI: 10.1002/gcc.10307
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and overexpression of the IGF2 regulator PLAG1 in hepatoblastoma

Abstract: There is evidence that 8q amplification is associated with poor prognosis in hepatoblastoma. A previous comparative genomic hybridization analysis identified a critical region in chromosomal bands 8q11.2-q13. Using restriction landmark genomic scanning in combination with a virtual genome scan, we showed that this region is delineated by sequences within contig NT_008183 of chromosomal subbands 8q11.22-q11.23. A real-time PCR-based genomic copy number assay of 20 hepatoblastomas revealed gain or amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 34 publications
1
94
0
1
Order By: Relevance
“…In this study, HB tumours with PLAG1 mRNA expression showed and tended to show higher levels of P4 and P3 transcripts, respectively. Thus, the correlation of PLAG1 mRNA expression with increased levels of P3 transcripts reported by Zatkova et al (2004) may be confirmed; furthermore, the correlation of PLAG1 mRNA expression with increased levels of P4 transcripts was also suggested.…”
Section: Loss Of Imprinting Ofmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, HB tumours with PLAG1 mRNA expression showed and tended to show higher levels of P4 and P3 transcripts, respectively. Thus, the correlation of PLAG1 mRNA expression with increased levels of P3 transcripts reported by Zatkova et al (2004) may be confirmed; furthermore, the correlation of PLAG1 mRNA expression with increased levels of P4 transcripts was also suggested.…”
Section: Loss Of Imprinting Ofmentioning
confidence: 63%
“…PLAG1 located in 8q11 encodes a developmentally regulated transcription factor, and positively regulates IGF2. The P3 promoter region of IGF2 contains PLAG1 consensus-binding sites, and PLAG1 transactivates the transcription from embryonic IGF2 promoter P3 in HB cell lines, HuH6 and HepG2 (Zatkova et al, 2004). PLAG1 mRNA was highly expressed in most HB tumours compared with normal liver tissues.…”
Section: Loss Of Imprinting Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…PLAG1 encodes for a transcription factor whose ectopic expression can trigger the development of several benign mesenchymal tumors (41). Indeed, the overexpression of PLAG1 is typically triggered by chromosomal translocations or, in rarer cases, by amplifications (42). PLAG1 and HMGA2 translocations are both frequent and mutually exclusive in pleomorphic adenomas of the salivary gland (43).…”
Section: Discussionmentioning
confidence: 99%
“…Other target genes such as CRLF1, CRABP2, CRIP2, PIGF are strongly induced in cells with PLAG1 induction. PLAG1 is a proto-oncogene whose ectopic expression can trigger the development of lipoblastomas and pleomorphic adenomas of the salivary gland (Hensen et al, 2002;Voz et al, 2004;Zatkova et al, 2004) (GeneCards GCID:GC08M057073 (http://www.genecards.org/cgibin/carddisp.pl?gene=PLAG1), UniProt Q6DJT9-PLAG1_HUMAN (http://www.uniprot.org/uniprot/Q6DJT9)).…”
Section: Plag1mentioning
confidence: 99%